Low-dose SoluMatrix diclofenac: a review of safety across two Phase III studies in patients with acute and osteoarthritis pain. (August 2015) - Gibofsky, Allan; Altman, Roy; Daniels, Stephen; Imasogie, Olaolu; Young, Clarence
Abstract : Introduction: Similar to other NSAIDs, diclofenac is associated with serious dose-related cardiovascular, gastrointestinal, and renal adverse events. Low-doseSoluMatrix diclofenac, containing submicron particles of diclofenac, was developed to provide effective analgesia at lower drug doses compared with currently available NSAIDs. Areas covered: The efficacy and safety of low-dose SoluMatrix diclofenac was evaluated in two randomized, placebo-controlled Phase III studies: a study in patients with acute pain following bunionectomy surgery and a study in patients with osteoarthritis pain of the hip or knee. In this review article, we summarize safety data from these studies. Expert opinion: The safety results from the Phase III studies indicate that all dosing regimens of low-dose SoluMatrix diclofenac up to 12 weeks are generally well tolerated. Few serious gastrointestinal, cardiovascular, renal, or hepatic adverse events commonly associated with NSAID use were reported in these studies. Although not directly compared, the safety of SoluMatrix diclofenac was similar to findings for other diclofenac drug products. The potential for safe and effective management of acute and chronic pain at reduced NSAID doses is attractive; definitive characterization of SoluMatrix diclofenac safety requires confirmation by long-term studies.